Economic Plants of Tripura State XI. Plants Yielding Oil Used for Nonedible Purposes - Deb, D. B. (Indian Forester, 1981)
The present paper entitied ’Economic plants of Tripura State XI. Plants yielding oil used for nonedible puroposes gives an account of the source of oil used for nonedible proposes as found in the State.